28 - 9x = -12 - 11x
as you say, add 9x to both sides, and you get
28 = -12 - 2x
Now add 12 to both sides and you get
40 = -2x
Now divide by -2 and you get
-20 = x
There's no reason to add 11x to both sides after all the x's are together. If you did do that, you have
28-9x+9x+11x = -12-11x+9x+11x
2x+11x = -12+9x
and you're no better off than when you started.
how do I solve 28 - 9x = -12 - 11x
I tried adding 9x to both sides adding 11x to both sides and doing a million different methods and after i got an answer I went to check it and it was wrong I really don't understand how to do these types of equations
1 answer